Musculoskeletal Disorders among Housekeeping Staff in Hospitals of Lahore - Anam Anwar, Zainab Hassan, Sehar Asjad, Kiran Saleem, Shabana Kauser, Zaryyab, Waqas Latif (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Repetitive injuries are among the top most musculoskeletal problems in present day lifestyle, among these upper extremities are the most vulnerable. Aim: To determine the prevalence of musculoskeletal disorders among housekeeping staff in hospitals of Lahore. Study design: Cross sectional study. Methodology: Total of 260 participants were included. Data was collected from General and Jinnah Hospitals of Lahore. A modified Nordic Musculoskeletal Questionnaire (NMQ) was used for assessing the prevalence of musculoskeletal disorders. The collected data was analyzed by using SPSS version 25. Chi square ware applied with P-value< 0.05 as significant. Results: The result showed that 159 (61.25%) were males and 101 (38.8%) were females. Majority of housekeeping staff did not missed their duty during the previous week in spite of musculoskeletal pain. Conclusion: It was concluded that overweight and obese workers were more prone to had musculoskeletal pain thus this affected their quality of life.